Fusobacterium nucleatum promotes metastasis of breast cancer via the miR-21-3p/FOXO3 axis - Huang, Yiping; Guo, Zhongzhong; Zeng, Zhaoyou; Shang, Chenyu; Zhang, Yingfeng; Ran, Ziwei; Luo, Guoqing; Shen, Sandi; Liu, Yaqin; Zhou, Peng; Ma, Peng; Zhang, Yanxia; et al. (Frontiers in Oncology, 2025)
PurposeThis study aims to investigate the impact of Fusobacterium nucleatum (F. nucleatum) infection on distant metastasis in breast cancer and its underlying mechanisms.MaterialsClinical breast cancer samples were collected, and F. nucleatum was identified through bacterial isolation and culture. In vitro and in vivo infection models were established using the isolated bacteria. The impact of F. nucleatum infection on breast cancer cell proliferation and migration was evaluated. High-throughput sequencing and bioinformatics analyses were performed to identify microRNAs exhibiting significant expression changes following F. nucleatum infection. Gene knockdown of miR-21-3p was utilized to assess its role in F. nucleatum-mediated epithelial-mesenchymal transition and cell migration. Online databases predicted the downstream targets of miR-21-3p, which were subsequently validated in cell models. Additionally, the effect of silencing FOXO3 on F. nucleatum-induced cell migration was examined.ResultsBoth in vitro and in vivo experiments showed that F. nucleatum infection did not affect cell proliferation but significantly enhanced EMT and migration. miR-21-3p was significantly upregulated after infection, and silencing it reduced F. nucleatum-induced migration. FOXO3 was identified as a downstream target of miR-21-3p, and silencing FOXO3 further enhanced cell migration.ConclusionF. nucleatum promotes breast cancer cell migration through the miR-21-3p/FOXO3 pathway. This study highlights the role of F. nucleatum in breast cancer metastasis and suggests potential therapeutic targets for intervention.